Biosurfactants produced by Pseudomonas syringae pv tabaci: A versatile mixture with interesting emulsifying properties. (October 2020) - Haidar, Carla N.; Pereira, Matheus M.; Lima, Álvaro S.; Nerli, Bibiana B.; Malpiedi, Luciana P.
Graphical abstract: Highlights: Interfacial activity of biosurfactants produced by P. syringae pv. tabaci. Chemical characterization revealed that the sample mostly consists of lipopeptides. Water surface tension of 29 mN/m was reached in presence of 5 % w/w of NaCl. Emulsifying activity comparable or even superior to that of commercial bioemulsifiers. Emulsions resulted to be little affected by different operational conditions. Abstract: In recent years, worldwide awareness about environmental concerns has led to an extensive searching for products of natural origin. Biosurfactants (BS), are an attractive alternative to the chemical counterparts. In these sense, this works evaluate for the first time the emulsifying and surface activity of biosurfactants produced by P. syringae pv. tabaci . Chemical characterization revealed that the produced BS extract mostly consisted in a mixture of syringopeptins and arthrofactins. Besides, this sample was able to reduce water surface tension up to 36.89 mN/m. This activity was improved by modifying conditions of pH, temperature and salinity. For instance, the surface tension was reduced up to 29 mN/m when using NaCl 5 % w/w. The BS also exhibited a high emulsifying activity, this being comparable or even superior to that of commercial bioemulsifiers such xanthan, tara and guar gums. A notorious emulsification index, close to 90 %, was exhibited by BS in coconut oil/water mixtures. Moreover, emulsifying activity resulted to be little affected by different operational conditions, thus retaining about 80 % of its emulsificant index in presence of 20 % w/w of NaCl at 80 °C. These findings are indicative of the BS promising properties and its potential as additive in a variety of industrial applications.